The The Correlation Between Participation In Pregnancy Workouts And Perineum Ruptures Incidence In Woman With Normal Labor At The Sumengko Village Maternity Cottage, Lamongan District - khusnul nikmah; Eka Sarofah Ningsih; Vita Yushofa (Universitas Nahdlatul Ulama Surabaya, 2021)
Labor often results in tearing of the perineum during labor when it is fully opened, the head enters the lower segment of the uterus then presses on the vulva, the head is born and the baby performs an external rotation so that the baby is born. It is in this phase that will affect the occurrence of the birth canal tear. Retrospective research method with case control analytic survey design. The sample technique used quota sampling of 25 respondents, using primary data. Data analysis used Chi Square. Contingency coefficient statistical test with the help of the SPSS program results P value 0.000 <α 0.05. If the P value is 0.000 <α 0.05, it means that there is a relationship between pregnancy exercise participation and the incidence of perineal rupture during normal delivery at Sumengko Polindes, Kedungpring Sub-District, Lamongan District. One of the right ways to anticipate the occurrence of perineal rupture is routine pregnancy exercise.